Ministry of Education, Guyana Education Sector Program Project - P174244: Labour Management Procedure - Guyana. Ministry of Education (Ministry of Education, Guyana, 2021)
The Government of Guyana has prepared a draft Education Sector Plan (ESP) 2020-2024 – Vision 2030. The ESP sets five priorities: (a) Improving governance and accountability; (b) Improving performance at all levels; (c) Improving the efficiency of the education system; (d) Reducing inequities in education; and (e) Contributing to lifelong learning and employability.
Keywords: education sector programme; lifelong learning